The development of intensity-duration-frequency curves for Pahang - Nur Asma', Suhaimee (2015)
In past few years, Pahang was experienced flooding in certain area and it getting worse by year with heavy rainfall especially at low level area cause of clog drain, design failing, wrong estimation and other natural causes. IDF curve use to design rainfall data by estimate peak discharge from IDF curve for engineering design such drainage, flood elevation, and other hydraulic design. This study purpose to develop intensity-durationfrequency (IDF) curve for all 12 district in Pahang based on this past year data and compare it with Log-Person Type III method than Gumbel method that use in Urban Storm Water Management (MSMA) to compare the differences value of IDF curve using both method. IDF curve requires rainfall data from the Department of Irrigation and Drainage (DID) for period of 5 minutes to 72 hour starting on year 1990 to year 2014. To designing IDF curve, process involved are find the missing data from nearest station, mean, standard deviation, frequency factor, and intensity value for 2, 5, 10 ,20, 50 and 100 years return period for both methods Gumbel and Log-Pearson Type III. Both methods, Gumbel and Log-Pearson Type III is compared to see the different value given by both methods. To test the accuracy of both methods, Komogorov Smirnov (KS) was constructed for fitting distribution. Based on the result, Gumbel method give clear trend than Log-Pearson Type III with 26.92% test accepted from 78 tests while Log-Pearson Type III almost all test was rejected.